Insomnia, its Prevalence, Associated Factors and Effects on Old Age: A Cross-Sectional Study - Pokharel, Bandana; Sharma, Bhaskkar; Acharya, Anup (Journal of Lumbini Medical College, 2018)
Introduction: Insomnia is a common problem among old age population. Almost half of all old age adults report difficulty in initiating and maintaining sleep. The objective of this study was to assess the prevalence of insomnia, its associated factors and effects in old age adults. Methods: This was an observational analytical study where adults above 60 years of age from a ward of a village development committee were included. Data were collected for a period of four months. Insomnia was measured by Athens Insomnia Scale and structured questionnaires were used to assess the effects of insomnia. Descriptive statistics were presented as frequency and percentages. Association between variables was assessed with Chi-square test or Fisher's Exact test as appropriate. Results: There were a total of 55 participants in the study. Insomnia was prevalent in 56.4% (n=31) of the study population. Among the studied socio-demographic variables, presence of medical illness was significantly associated with insomnia. Insomnia was significantly associated with morning headache, irritability, unhappiness, fatigue, lack of concentration, day time sleepiness, avoiding interaction with people, and need of sedative for sleep. Conclusion: Majority of the old age adults suffer from insomnia with night awakenings as the most common symptom. Insomnia significantly affects various aspects of life at an old age. DOI: https://doi.org/10.22502/jlmc.v6i2.256